Innovation Through Business Modeling: Steps to Corporate Success - Ida Hindarsah (SEAN Institute, 2023)
With rapid changes in the business environment, companies need to understand and integrate innovation as a key element to achieve long-term success. This study will explore concrete steps in implementing business modeling that can become the basis for creating and managing innovation efficiently. Therefore, this research aims to investigate the role of innovation in improving company performance through the application of effective business modeling. This research uses a qualitative approach with descriptive methods. The research results show that innovation through business modeling has a crucial role in increasing company success amidst a dynamic business landscape. In the face of the declining average lifespan of business models, companies need to actively adopt innovative measures to strengthen core businesses, drive rapid growth, and respond to industry changes. The research findings emphasize the importance of customer segment analysis, developing intelligent revenue models, and implementing effective distribution channels. Additionally, research highlights the need to establish a strong innovation culture within organizations to increase adaptability and responsiveness to external and internal changes